EFEKTIVITAS PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM TEMPAT PENGOLAHAN SAMPAH REDUCE, REUSE, RECYCLE (TPS 3R) SEKAR TANJUNG DI DESA SANUR KAUH, KECAMATAN DENPASAR SELATAN - Irdanti, Olivia Blessiane; Yudharta, I Putu Dharmanu; Purmaningsih, Putu Eka (CITIZEN CHARTER, 2021)
TPS 3R Sekar Tanjung was built as the first pilot project of Extended Stakeholder Responsibility (ESR) waste management system that empowers communities in the waste processing process. In its implementation, TPS 3R Sekar Tanjung experienced obstacles in the form of low community participation, lack of infrastructures, and lack of technological knowledge. The purpose of this research is to determine the effectiveness of community empowerment carried out through TPS 3R Sekar Tanjung program in the village of Sanur Kauh. Data were collected using semi-structured interviews, observation, documentations and analyzed using Duncan's Theory of Effectiveness along with Winarni’s Concept of Community Empowerment. The results showed that community empowerment carried out at TPS 3R Sekar Tanjung was not fully effective yet even though it had run optimally. TPS 3R Sekar Tanjung has succeeded in achieving their goals, integration, and enabling but has not fulfilled the indicators of adaptation, empowering and self-sustaining the society. Keywords: Effectiveness, Community Empowerment, Garbage Dump, Waste Management